Phytocemical Screening Water Extract of Pineapple Skin (Ananas comosus (L.) Merr) from East Lombok - Angelina, Varelia; Solehah, Kurnia; Hasina, Raisya (Jurnal Biologi Tropis, 2024)
Pineapple (Ananas comosus (L.) Merr) is empirically used as a medicine to cure constipation, nausea, urinary tract disorders, flu, and various skin diseases. Secondary metabolites that cause this activity are alkaloids, tannins, flavonoids, saponins and triterpenoids. Secondary metabolite phytochemical screening has been carried out on pineapple peel juice and freeze-dried pineapple peel powder, but no tests have been carried out on dehydrated pineapple peel powder. The primary objective of this study was to determine of secondary metabolites in pineapple peel water extract. The powdered pineapple peel extract was made using pineapple peel juice that had been dried in a dehydrator at 40ºC for two 24-hour cycles. Phytochemical screening makes use of a tube test, which involves qualitative observation using separate reagents for each chemical. Alkaloids, flavonoids, quinones, tannins, and triterpenoids were found in pineapple skin as secondary metabolites, but saponin chemicals were found to be absent.